Avenue of Saman [sic] Trees, Trinidad, B.W.I .- 20797 - (:unkn) unknown (Photogelatine Engraving Co. Limited, 2010)
The postcard shows an avenue lined with Samaan trees. This postcard is addressed to Miss Anna Stieff, the location of the postcard is unclear. Affixed to the postcard is a 24 and a 6 cents Trinidad and Tobago postage stamp.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Rural roads--Trinidad and Tobago; Albizia saman; Samaan tree